Features of Dielectric Properties of 0.20BiScO3·0.45PbTiO3·0.35PbMg1/3Nb2/3O3 Samples Obtained by the Melt-Hardening Method - A. A. Nogai; A. S. Nogai; D. E. Uskenbaev; E. A. Nogai (Ceramics)
This paper studies the structural parameters and electrophysical properties (dielectric and piezo electric, as well as currents of thermostimulated depolarization) of samples of composition 0.20BiScO3·0.45PbTiO3·0.35PbMg1/3Nb2/3O3 (or in short 0.20BS·0.45PT·0.35PMN) obtained by ceramic and melt-hardening methods of synthesis. In the ceramic method, the samples were obtained from the starting oxides by two-stage firing. In the melt method, amorphous precursors were first obtained from heat-treated and non-heat-treated starting oxide mixtures by melting and subsequent quenching under sharply gradient temperature conditions. Samples were obtained after grinding, pressing, and thermal annealing of the synthesized precursors, and four types of samples differing in size and shape of the intermediate precursor particles (crystallites) were obtained. The X-ray phase analysis showed that the predominant phase in the studied samples is the perovskite phase; in both types of samples, up to 5 wt.% of impurity phase with pyrochlore structure was also present. The samples of 0.20BS·0.45PT·0.35PMN exhibit dielectric properties characteristic of relaxor ferroelectrics, and the polarized samples exhibit a pronounced piezo effect with a piezo modulus value of d33~200 pC/N. A comparative analysis of the properties of the samples obtained by different methods has been carried out. The essential advantage of the melt method is that its use allows obtaining varieties of four kinds of ferroelectric relaxors and reduces the time of synthesis of samples by 2–3 times.